Síntese e caracterização de complexos de Prata (I): investigação da citotoxidade e interação com o DNA - Rocha, Josias da Silveira (2020)
The inorganic compound, cisplatin, is used on a large scale to different types of cancer. This complex acts in DNA structure by covalent bonds. However, the chemotherapy agent presents several side effects and some tumors are resistant to the treatment with cisplatin. Thus, new researches are necessary to find more specific agents with different modes of action. Intercalation provides severe damage to DNA structure initiating the apoptosis process. Therefore, the aim of our work was the synthesis and characterization of five new silver (I) complexes of the type [Agn(R-L)n(tu)2](NO3)2, where n = 1 or 2, R-L = extended ligand with substituents CH3, Cl, NO2, CN(nitrile) and NON (furazan), tu = thiourea. The molecular structures were proposed by spectroscopic analysis (UV-Vis, IR, NMR), elemental analysis, molecu-lar conductometry, and X-ray diffraction when obtained single crystals. All compounds had their cytotoxicities investigated against prostate tumor cells (DU-145) and cisplatin-resistant ovarian carcinoma (A2780cis), standing out among them the complexes [Ag(NON-L4)(tu)2]NO3 and [Ag2(CN-L5)2(μ-tu)2](NO3)2 who had low IC50 values in the range at 0,403-6,36 µM being more actives than cisplatin. The structur-al features of these compounds are promising to develop new silver (I) complexes with high anticancer activities.